Photodegradation of herbicide Metsulfuron-methyl with TiO2 supported on magnetite particles coated with SiO2 - Montañez, Juan Paulo (2018)
Natural watercourses may be significantly contaminated due to the increase of agricultural activities, making it necessary to develop new methodologies for the remediation of agrochemicals, including herbicides. To this effect, photodegradation with TiO2 is a very effective process. However, this semiconductor cannot be easily removed from the treated aqueous medium. Supporting the photocatalyst on different materials facilitates its removal by several methods, including magnetic attraction. According to this goal, this work reports the synthesis of TiO2 photocatalysts supported on SiO2-coated magnetite particles (Fe3O4) by a lowerature sol-gel process (75â€ °C). By varying the aging time of the TiO2 sol, materials with different structural properties and combinations of anatase-brookite phases were obtained. Of all the synthesized solids, the one with the highest photocatalytic activity in the degradation of model compounds was the TiO2/SiO2/Fe3O4 catalyst with a 47.4/13.6/39.0â€ wt % respectively. Under optimal working conditions and at a pH value close to neutrality (conditions in which Metsulfuron-methyl is persistent in an aqueous medium) this catalyst degraded 70% of the herbicide initial concentration in three and a half hours of artificial irradiation with an activity similar to the mass TiO2. The aging time significantly influenced on structural properties of supported TiO2. With its increase, the degree of crystallinity of the samples also increased but its specific surface decreased. The catalyst with higher photoactivity blends the best combination of both factors and is, therefore, a good alternative for the remediation of contaminated effluents with commercial formulations of this herbicide. Also, its magnetic support facilitates its subsequent removal from treated water samples.